Near-Miss Transcription Errors: A Comparison of Reporting Rates between a Novel Error-Reporting Mechanism and a Current Formal Reporting System. Issue 2 (February 2015) - South, David A.; Skelley, Jessica W.; Dang, Mary; Woolley, Thomas
Purpose: The medication use process comprises several steps. In institutions without full implementation of computerized prescriber order entry (CPOE), transcription is a critical step in this process. As focus is increasingly placed on identifying near-miss errors, this study aimed to compare near-miss transcription error (NMTE) reporting rates between an institution's formal reporting system and an NMTE reporting mechanism. Methods: Two NMTE reporting mechanisms were assessed for 3 months. These mechanisms included the institution's formal error-reporting system and a specific transcription error queue within the institution's order imaging software. Date, patient-care unit, and type of transcription error were recorded for each order image in the transcription error queue and for each transcription error reported formally. Following data collection, reporting rates for both systems were compared. Results: Data collection spanned 92 days and an estimated 460, 000 medication orders. In total, 1, 563 NMTEs were reported using the transcription error queue and 12 errors were reported via the formal reporting mechanism. Of the 1, 563 errors identified via the transcription error queue, 325 (20.79%) were of an unknown type. Reporting rates (with unknown errors removed) were 0.27% and 0.0026% for the novel system and formal reporting system, respectively ( P < .001). Conclusion: Significantly more NMTEs were reported utilizing the novel system compared with the formal reporting system.